Factors influencing detection of Potato Leafroll Virus and Potato Virus y in potato tuber extracts. - Treder, Krzysztof; Przewodowski, Włodzimierz; Barnyk, Agnieszka (Plant Breeding and Seed Science, 2009)
Detection of Potato leafroll virus (PLRV) and Potato virus Y (PVY) directly in potato tubers has been influenced by several factors. The most important were: the place of tuber sampling, preincubation of tuber sap before loading into wells of microplate and duration of tubers storage after collecting from field. The concentration of both viruses was highest in the heel part of tubers, whenever tested. Preincubation of tuber sap for several hours improved true/false signal ratio for dormant tubers and enabled reliable detection of both viruses. However after natural dormancy breaking it was necessary to change Cocktail-ELISA procedure to obtain reliable results, consistent with DAS-ELISA on leaves. The sap was not preincubated but loaded into wells directly after sample collecting and immuno-enzymatic reaction was developed overnight in refrigerator...